Gaseous and adsorbed PAH in an iron foundry. - Knecht, U (1986)
The increased risk of lung cancer among foundry workers is assumed to be associated with the inhalation of gaseous and particle bound polycyclic aromatic hydrocarbons (PAH). These compounds are produced during pyrolysis of carbon containing loading material in the moulding sand. The concentrations of 20 PAH, some of which are carcinogenic, have been determined in the dusty casting area of an iron foundry by means of gas chromatography and mass spectrometry. The total dust was fractionated by means of a precision cascade impactor. It was possible to differentiate the PAH load in microgram/mg dust in seven particle size fractions ranging from 0.36- greater than or equal to 24.95 microns. Initially, there was an increase of the adsorbed PAH mass concentration with increasing particle diameter up to a maximum of 1.1 microgram/mg in the dust of the 1.57 micron fraction. Thereafter there was a continuous decrease of PAH mass concentration with increasing particle size. When the differing weights of the seven fractions are taken into account, however, the total PAH load of the individual fractions increases steadily with increasing particle size. The inhalable fine dust, 31.4% of the total dust, contains 49.9% of the total adsorbed PAH. The gas phase contained on average three times more carcinogenic PAH with four and five rings than was adsorbed on the dust. Thus the percentage of the gaseous substances amounts to 77% of the total PAH load at the place of work in an iron foundry.